Audiovisual crossmodal cuing effects in front and rear space - Lee, J; Spence, C (Frontiers Media SA, 2015)
The participants in the present study had to make speeded elevation discrimination responses to visual targets presented to the left or right of central fixation following the presentation of a task-irrelevant auditory cue on either the same or opposite side. In Experiment 1, the cues were presented from in front of the participants (from the same azimuthal positions as the visual targets). A standard crossmodal exogenous spatial cuing effect was observed, with participants responding significantly faster in the elevation discrimination task to visual targets when both the auditory cues and the visual targets were presented on the same side. Experiment 2 replicated the exogenous spatial cuing effect for frontal visual targets following both front and rear auditory cues. The results of Experiment 3 demonstrated that the participants had little difficulty in correctly discriminating the location from which the sounds were presented. Thus, taken together, the results of the three experiments reported here demonstrate that the exact co-location of auditory cues and visual targets is not necessary to attract spatial attention. Implications of these results for the design of real-world warning signals are discussed.